HSV-1 Modulates IL-6 Receptor Expression on Human Dendritic Cells - Birzer, Alexandra; Krawczyk, Adalbert; Draßner, Christina; Kuhnt, Christine; Mühl-Zürbes, Petra; Heilingloh, Christiane Silke; Steinkasserer, Alexander; Popella, Linda (Frontiers in Immunology, 2020)
Dendritic cells (DCs) are the guardians of the immune system since they are located in the majority of peripheral tissues. In addition, they are crucial for the induction of an effective immune response based on their unique capacity to stimulate naive T cells. During co-evolution, the human pathogen herpes simplex virus type 1 (HSV-1) has evolved several immune evasion mechanisms in order to subvert the host’s immune system especially by targeting DC biology and function. Here we demonstrate that HSV-1 infection influences the IL-6 receptor (IL6R) expression both on protein and mRNA levels in/on human monocyte-derived mature DCs (mDCs). Surprisingly, reduced IL6R expression levels were also observed on uninfected bystander mDCs. Mechanistically, we clearly show that HSV-1-derived non-infectious light (L-) particles are sufficient to trigger IL6R regulation on uninfected bystander mDCs. These L-particles lack the viral DNA-loaded capsid and are predominantly produced during infection of mDCs. Our results show that the deletion of the HSV-1 tegument protein vhs partially rescued the reduced IL6R surface expression levels on/in bystander mDCs. Using a neutralizing antibody, which perturbs the transfer of L-particles to bystander mDCs, was sufficient to rescue the modulation of IL6R surface expression on uninfected bystander mDCs. This study provides evidence that L-particles transfer specific viral proteins to uninfected bystander mDCs, thereby negatively interfering with their IL6R expression levels, however, to a lesser extend compared to H-particles. Due to their immune-modulatory capacity, L-particles represent an elaborated approach of HSV-1-mediated immune evasion.